Perubahan Kepemimpinan dalam Lembaga Pendidikan Islam: Dampak Krisis Kepercayaan Masyarakat terhadap Pengelolaan dan Keberlanjutan - Muharirul Umam Adi Permana (Visionaria: Journal of Educational Innovation Management, 2025)
Leadership transitions in Islamic educational institutions are not merely administrative events; they often trigger structural disruptions and public trust crises. This study aims to analyze the impact of leadership transitions on institutional management, organizational social relations, and community trust as the foundation for institutional sustainability. Employing a qualitative approach with a case study design, the research was conducted at TPQ Al-Abror, Blado Wetan, Probolinggo. The research subjects included former and current leaders, teaching staff, students’ parents, and community figures selected purposively. Data collection techniques involved participatory observation, semi-structured interviews, and institutional documentation, analyzed using Miles and Huberman’s interactive model with triangulation for data validation. The findings reveal that the absence of a systematic leadership transition mechanism contributes to policy inconsistency, operational instability, program stagnation, and declining community participation. Communication gaps among management and lack of transparency exacerbate internal fragmentation and widen the social distance with the community. The underperformance of the institution’s public relations functions further hinders efforts to improve institutional image and restore public trust. The novelty of this study lies in its analytical focus on small-scale, community-based Islamic institutions, which have received limited academic attention. The findings imply the need for deliberate and collaborative leadership transition strategies, strengthened institutional communication, and active community engagement as partners in educational governance to ensure long-term sustainability.